Middle Cerebral Artery Pulsatility Index for Prediction of Successful Induction of Labour in Postdated Pregnancy: A Prospective Observational Study - Yashi Nagar; Rekha Bharti; Kajal Baleja; Amita Malik; Divya Pandey; Jyotsna Suri (Journal of Clinical and Diagnostic Research)
Introduction: Postdated pregnancy is the most frequent indication for Induction of Labour (IOL). The foetal Middle Cerebral Artery Pulsatility Index (MCA PI) is assessed to predict foetal wellbeing in cases of late foetal growth restriction. It has also been studied as a predictor of IOL and is reported to be more sensitive than the conventional Bishop score. Aim: To evaluate the MCA PI as a predictor of successful labour induction in postdated pregnancy. Materials and Methods: This prospective observational study was conducted in obstetrics wards of Safdarjung Hospital over a period of 15 months, including 296 nulliparous women with singleton postdated pregnancy admitted for IOL. After obtaining a detailed history and conducting a physical examination, per vaginal examination for Bishop’s score and transabdominal ultrasound for foetal MCA Doppler was done. Women were followed for progression to active labour, and mode of delivery was noted. Primary outcome measure was successful IOL, defined as women entering active phase of labour, which is defined as cervical dilation of >5 cm. Other outcome measures studied included the induction to active phase interval, induction to delivery interval and mode of delivery. Receiver Operating Characteristics (ROC) curve was used to find out Area Under Curve (AUC) for MCA PI and Bishop score for predicting successful IOL. De Long et al., test was used to compare AUC. Univariate and multivariate logistic regression was used to assess the predictors of successful labour induction. A p-value of <0.05 was considered statistically significant. Results: Out of 296 women enrolled in the study, 285 women (96.3%) had successful IOL. Around 281 (98.9%) women with successful IOL had a vaginal delivery. At a cut-off of <1.67, MCA PI had a sensitivity of 100%, a specificity of 99.3%, a Positive Predictive Value (PPV) of 84.6%, a Negative Predictive Value (NPV) of 100%, and diagnostic accuracy of 99.3%, for prediction of successful IOL. MCA PI had almost perfect reliability for predicting the outcome of labour induction, Kappa=0.91 and Youden index score of 99.3. Conclusion: MCA PI is a good predictor of successful labour induction in nulliparous women with postdated pregnancy.